2022
DOI: 10.1080/14786419.2022.2110093
|View full text |Cite
|
Sign up to set email alerts
|

α-Glucosidase inhibitory derivatives of protocetraric acid

Abstract: Lichen-derived depsidones have been a successful source for alpha-glucosidase inhibitory agents with numerous advantages. In this paper, derivatives of protocetraric acids were designed and synthesized. Diels-Alder reaction, esterification, and Friedel-Crafts alkylation of protocetraric acid with different reagents under Lewis acid were performed. Eleven products were prepared, including 10 new compounds and parmosidone A. Among them, compounds 2-4 and 6 had the novel skeletons. The newly synthetic products we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…This indicated the important role of the depsidone scaffold in α ‐glucosidase inhibition. The results were consistent with previously reported depsidones from Parmotrema lichens [8–11,15–16] . Noteworthy, the difference in α ‐glucosidase inhibitory activity between 1 and 2 suggested that the phenolic (D‐ring) and oxotetrahydrofuranyl moieties in 1 was possibly decrease in inhibitory activity against α ‐glucosidase.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This indicated the important role of the depsidone scaffold in α ‐glucosidase inhibition. The results were consistent with previously reported depsidones from Parmotrema lichens [8–11,15–16] . Noteworthy, the difference in α ‐glucosidase inhibitory activity between 1 and 2 suggested that the phenolic (D‐ring) and oxotetrahydrofuranyl moieties in 1 was possibly decrease in inhibitory activity against α ‐glucosidase.…”
Section: Resultssupporting
confidence: 92%
“…[1 -5] Several lichen extracts have been used in folk medicine, and some lichen metabolites have been shown to have antifungal, [6] antimicrobial, antioxidant, and insecticidal [7] properties. Lichen-derived depsidones are thought to be potent α-glucosidase inhibitors, [8][9][10][11] as are natural para-and meta-depsidones. [8,9] The lichen Parmotrema cristiferum (Taylor) Hale (Parmelia-ceae) occurs commonly in high-altitude forests in Vietnam.…”
Section: Introductionmentioning
confidence: 99%
“…According to molecular docking analyses, there is a greater potential for pharmacological effect when evaluating isolated compounds present in the extracts of Psoroma species, which is evident with other Antarctic lichen species, such as H. lugubris where the isolation of compounds such as usnic acid, barbatolic acid, atranol, and 5,7-dihydroxy-6-methylphthalide demonstrates greater antioxidant and enzyme inhibition activity (Areche et al, 2022); likewise, computational studies carried out with compounds present in the extracts of other Antarctic species, such as L. brialmontii, P. pubescens, S. globosus, C. gracilis, and C. chlorophaea (Torres-Benítez et al, 2022;Torres-Benítez et al, 2023a), validate the promising use of compounds of phenolic nature for the treatment of different pathologies of wide prevalence and incidence as well as the understanding of their mechanisms of action at the organismic and cellular level (White et al, 2014). In addition, in the last 2 decades, biologically active metabolites have been isolated, such as atranorin (Melo et al, 2011;Zhou et al, 2017;Urbanska et al, 2022), barbatic acid (Reddy et al, 2019), diffractaic acid (Karagoz et al, 2015;Emsen et al, 2018), evernic acid (Fernandez-Moriano et al, 2017a;Shameera Ahamed et al, 2019;Lee eta al., 2021), fumarprotocetraric acid (Kosanić et al, 2014;Fernández-Moriano et al, 2017b), gyrophoric acid (Candan et al, 2006;Bačkorová et al, 2011), lobaric acid (Hong et al, 2018), physodic acid (Studzińska-Sroka et al, 2021b), protocetraric acid (Nguyen et al, 2023), thamnolan (Omarsdottir et al, 2007), usnic acid (Luzina and Salakhutdinov, 2018), and vulpinic acid (Varol et al, 2016;Kılıç et al, 2018), which are present in the species of the genera Cladonia, Parmotrema, Lepraria, Lethariella, Pseudoevernia, Hypotrachyna, Umbilicaria, Usnea, among others.…”
Section: Evaluation Of Docking Pancreatic Lipase Inhibitionmentioning
confidence: 99%